2020
DOI: 10.1186/s12884-020-03244-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of postnatal care non-utilization among women in Demba Gofa rural district, southern Ethiopia: a community-based unmatched case-control study

Abstract: Background Maternal and neonatal mortality remain a significant problem across much of the developing world, especially in sub-Saharan Africa countries. In Ethiopia, most maternal and neonatal deaths occur during the postpartum period; this is a critical time for monitoring the health of women and newborns, but the most neglected period for care. In rural communities of Ethiopia, the utilization of postnatal care service is very low and evidence on which factors contribute to the non-utilization of postnatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…The results of the correlation test also showed significant results between the two variables (p=0.040). This finding is in line with the findings in previous studies, which informed that mothers who did ANC visits performed more postnatal care than mothers who did not carry out ANC visits 11,12 . This is because mothers who complete ANC will get counseling from midwives to carry out postnatal care so that mothers who do antenatal care will be more motivated to carry out postnatal care than mothers who do not make ANC visits 7,13 .…”
Section: Resultssupporting
confidence: 92%
“…The results of the correlation test also showed significant results between the two variables (p=0.040). This finding is in line with the findings in previous studies, which informed that mothers who did ANC visits performed more postnatal care than mothers who did not carry out ANC visits 11,12 . This is because mothers who complete ANC will get counseling from midwives to carry out postnatal care so that mothers who do antenatal care will be more motivated to carry out postnatal care than mothers who do not make ANC visits 7,13 .…”
Section: Resultssupporting
confidence: 92%
“…The result of this study showed that mother’s place of delivery had contributed for attending three PNC visits, this finding goes in line with a comparative report from developing countries that showed low proportion of mothers who delivered at home went for postnatal visits [ 6 , 33 ]. In Ethiopia, mothers are encouraged to deliver at health center and hospitals, where they can get skilled care at the intrapartum and postpartum periods.…”
Section: Discussionsupporting
confidence: 89%
“…Our dependent variable (PNC) for our third model will be measured as; a mother who left the delivery facility within 24 hours is considered as a non-utilizer of Postnatal Care and hence denoted by '0'. If she did stay at the delivery facility for more than 24 hours, she would be treated as a utilizer of postnatal care and denoted by '1' in our binary definition (Manote & Gebremedhin, 2020). We have used this measure to avoid the information loss we faced during the construction of the above-mentioned variable.…”
Section: Variablesmentioning
confidence: 99%